Quantification of nanoparticles at the single-cell level: an overview about state-of-the-art techniques and their limitations. (August 2014) - Vanhecke, Dimitri; Rodriguez-Lorenzo, Laura; D. Clift, Martin J.; Blank, Fabian; Petri-Fink, Alke; Rothen-Rutishauser, Barbara
With the increasing production and use of engineered nanoparticles it is crucial that their interaction with biological systems is understood. Due to the small size of nanoparticles, their identification and localization within single cells is extremely challenging. Therefore, various cutting-edge techniques are required to detect and to quantify metals, metal oxides, magnetic, fluorescent, as well as electron-dense nanoparticles. Several techniques will be discussed in detail, such as inductively coupled plasma atomic emission spectroscopy, flow cytometry, laser scanning microscopy combined with digital image restoration, as well as quantitative analysis by means of stereology on transmission electron microscopy images. An overview will be given regarding the advantages of those visualization/quantification systems, including a thorough discussion about limitations and pitfalls.